Re: Define x* by the equation x* = π-x. Then ((−π)*)* =
[#permalink]
06 Sep 2016, 13:30
"this: f(f(−π))
to this: f(π − (−π))"
Ignore the wrapper function (the extra f() ) for a moment...
The function is f ( x ) = π - x, so
f ( π ) = π - x -π
f ( π ) = π - ( - π )
Is that any clearer? If so...subtracting a negative is the same as adding.
π - ( - π ) = π + π
Why is there a question using an unusual function format instead of the standard f()? I do not question the why of GMAT! But I suspect it's testing your mental flexibility, that you grasp we're just dealing in symbols that we can arbitrarily define and that x* has nothing to do with the multiplication or exponential functions but is simply a function we're newly defining.